Monitoring the electrical resistivity of concrete using Arduino (International Journal of Geoscience, Engineering and Technology, 2021)
Electrical Resistivity is the physical property that has the capacity to resist the passage of electric current and this variable in concrete changes by several factors, with the water / cement (a/c) ratio being one of the most relevant. The a / c ratio is a parameter of paramount importance with regard to the quality of the concrete, due to its correlation with the compressive strength and durability of the concrete. The present work aimed to create a measurement system using the Arduino microprocessor to measure and record the electrical resistivity values of the concrete, testing its use in two concrete samples with 0,40 a/c and 0,60 a/c. The configuration of the electrodes to perform the electrical resistivity measurements was in accordance with the Wenner method. The results showed that the obtained values had a satisfactory precision. Thus, the Arduino project with proved to be a viable method for carrying out electrical resistivity measurements and analyzing the quality the of concretes.
Keywords: Arduino; Concrete; Electrical Resistivity